2020
DOI: 10.1007/s10639-020-10385-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of behavioural intention on podcast acceptance

Abstract: This research contributes to knowledge in mediating effect of lecturers’ behavioural intention towards the acceptance of podcasts technology in universities. A cross-sectional quantitative research design was involved in this study. Also, a total of eight hundred and twenty-nine (829) lecturers participated in this research from three different south-west Nigeria Federal universities. The research instrument was titled lecturer’s acceptance questionnaire (LAQ) with a calculated Cronbach’s alpha of .919, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 95 publications
(117 reference statements)
1
12
0
1
Order By: Relevance
“…The main choice is in the educational context when adopting technology as a learning tool [47], [48]. For the rest, we will concentrate on the publication history by researchers relating to the acceptance of technology as a defined topic [49], [50], [51], [52]. The picture below, illustrates that during the last 10 years, there have been several published research articles that were selected according to the criteria.…”
Section: Results a Overall Review Of Selected Studiesmentioning
confidence: 99%
“…The main choice is in the educational context when adopting technology as a learning tool [47], [48]. For the rest, we will concentrate on the publication history by researchers relating to the acceptance of technology as a defined topic [49], [50], [51], [52]. The picture below, illustrates that during the last 10 years, there have been several published research articles that were selected according to the criteria.…”
Section: Results a Overall Review Of Selected Studiesmentioning
confidence: 99%
“…Neither EFL curricula nor exams devote adequate space to teach and test higher-order thinking skills. A plausible reason of this result was provided by Ifedayo, Ziden, and Ismail (2021). They reported that university staff's as well as students' low-level behavioural intention negatively impacted podcast acceptance.…”
Section: Discussionmentioning
confidence: 97%
“…Perkembangan dan kemajuan perbankan syariah di Sumatera Barat masih jauh di bawah perbankan konvensional yang terdapat di Sumatera Barat, hal tersebut terlihat dari 67% masyarakat Sumatera Barat yang memiliki rekening bank, masih menggunakan bank konvensional sedangkan sekitar 43% lainnya yang menggunakan perbankan syariah. Sebagian nasabah yang menggunakan Bank Syariah sebagian besar berasal ikatan dinas antara instansi yang menjadi tempat mereka bekerja dengan perbankan syariah tertentu [2]. Dengan demikian terlihat sebagian besar masyarakat yang menggunakan jasa Bank Syariah bukan karena faktor sukarela.…”
Section: Pendahuluanunclassified